2019
DOI: 10.31590/ejosat.646266
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analizi Yöntemleri Kullanılarak Doğu Anadolu Bölgesi Aylık Yağış Miktarlarının Değerlendirilmesi

Abstract: Özet Bu çalışmada, Doğu Anadolu Bölgesi'ne düşen aylık ve yıllık toplam yağışların trend analizinin araştırılması hedeflenmiştir. Bu amaçla, Meteoroloji Genel Müdürlüğü'nün 46 adet yağış gözlem istasyonundan alınan, 1960 ile 2013 yılları arasında değişen, verilere Run testi ve Pettitt testi uygulanarak homojenlik analizi yapılmıştır. Homojen olduğu belirlenen istasyonlara Mann-Kendall testi ve Spearman'ın Rho testi uygulanarak trend analizi incelenmiş, Sen'in eğim metodu kullanılarak trendlerin eğimi belirlenm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…The trend analysis results of regions A, F and G were statistically significant at the level of 5%, and the decreasing trend of region E was statistically significant at the level of 10%. Şenocak and Emek (2019) reported similar results for region E. The effect of major weather systems linked to the large-scale atmospheric circulation can be used to explain that regions F and G had weaker correlations in rS values compared to other regions. The Mediterranean Region (G) showed a decrease in precipitation values, which is consistent with previous studies focused on the Mediterranean region conducted by Maheras et al (2004) and Kutiel and Türkeş (2017).…”
Section: Discussionmentioning
confidence: 57%
“…The trend analysis results of regions A, F and G were statistically significant at the level of 5%, and the decreasing trend of region E was statistically significant at the level of 10%. Şenocak and Emek (2019) reported similar results for region E. The effect of major weather systems linked to the large-scale atmospheric circulation can be used to explain that regions F and G had weaker correlations in rS values compared to other regions. The Mediterranean Region (G) showed a decrease in precipitation values, which is consistent with previous studies focused on the Mediterranean region conducted by Maheras et al (2004) and Kutiel and Türkeş (2017).…”
Section: Discussionmentioning
confidence: 57%
“…It revealed that 14 stations were not homogeneous according to the Pettitt test, which confirmed that it was more sensitive in detecting inhomogeneity for time series. Şenocak & Emek (2019) examined the homogeneity of Monthly Precipitation data of 46 meteorological stations in the Eastern Anatolia Region with the Run and Pettitt tests. The results showed that the data of seven stations according to the Pettitt test and one station according to the Run test were not homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…2001;Türkeş, 1996;Tayanç vd., 1997;Kadıoğlu, 1997;Çiçek, 2003;Tosic ve Unkasevic 2005;Karabulut ve Cosun, 2009;Emek, 2014;Addisu, vd. 2015;Polat ve Sunkar, 2017;Asfaw vd., 2017;Rahman, vd., 2017;Karaosmanoğlu ve Günek, 2018;Şenocak ve Emek, 2019;Coşkun, 2020a;2020b;2020d). Hidrografik havzalarda ise akım değişkeni önemle takip edilerek sıcaklık, yağış, buharlaşma gibi meteorolojik parametrelerle bağı oluşturulmalıdır.…”
Section: Introductionunclassified